Catalytic cracking of biomass tar over char supported nickel catalyst. (15th February 2018) - Hu, Mian; Laghari, Mahmood; Cui, Baihui; Xiao, Bo; Zhang, Beiping; Guo, Dabin
Abstract: Catalytic cracking of biomass tar was investigated using steam gasification obtained char supported nickel catalyst in a lab-scale fixed bed reactor to determine the effects of catalytic cracking temperature, Ni loading and gas residence time on product distribution and gas composition. Results showed that the optimum catalytic cracking parameters were at 800 °C catalytic cracking temperature, 6 wt% Ni loading and 0.5 s gas residence time. The characterizations of tars were determined by ultimate analysis, FTIR and GC-MS. Compared with no catalyst cracking, the relative content of single-ring aromatics in tars obviously increases with the appreciably decreases in polycyclic aromatics, O-containing compounds and heterocyclic compounds after catalytic cracking, especially in Ni-6/char catalyst condition. The surface characteristics of Pre- and Post- char supported 6 wt% loading Ni catalysts were analyzed with BET, SEM, XRD and XPS. The BET and SEM results indicated that there was a slight deposition of coke on the surface of char after catalytic cracking. Meanwhile, XRD and XPS results indicated that NiO was transformed into Ni via carbothermal and hydrogenation reductions which contributed to the enhancement of tar conversion. These findings manifested that char supported nickel catalyst can be used as a low-cost catalyst to decompose tar. Highlights: Steam gasification obtained char supported nickel catalysts were prepared for tar cracking. 6 wt% Ni loading catalyst shows good catalytic cracking performance. After catalytic cracking, the content of heavy polyaromatic hydrocarbons in tar reduced. Pre-Ni-6/char and Post-Ni-6/char catalysts were analyzed by BET, SEM, XRD and XPS. Mechanism of catalytic cracking of biomass over the char/char support catalyst was proposed.